Prototropic tautomerism of 9-methylguanine: quantum-mechanical investigation - Glushenkov, A.N.; Hovorun, D.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
For the first time, the full molecular-zwitterionic 9-methylguanine family has been obtained in vacuum, water, DMSO, and the ε = 4 continuum. It is shown that it consists of 14 molecular tautomers and 18 zwitterions, 9 of which are ylides.